Review of amphipods of the family Pleustidae Buchholz, 1874 (Amphipoda) from the coastal waters of Sakhalin Island (Far East of Russia). II. Subfamily Eosymtinae Bousfield & Hendrycks, 1994 - Labay, Vjacheslav S. (Zootaxa, 2022)
A taxonomic analysis of subfamily Eosymtinae Bousfield & Hendrycks, 1994 is performed. A review of subfamily Eosymtinae from the shelf of Sakhalin Island and adjacent area based on all literature and own data is provided. Based on new material, the new species Eosymtes magnumoculis sp. nov. is described from the shelf of Sakhalin Island and Kamchatka Peninsula. The range of Cognateosymtes serraticoxae Labay, 2018 is expanded. A key to the amphipod genera of the subfamily Eosymtinae is given. The key to the species of genus Eosymtes is provided.